2014 IEEE 8th International Symposium on Embedded Multicore/Manycore SoCs 2014
DOI: 10.1109/mcsoc.2014.24
|View full text |Cite
|
Sign up to set email alerts
|

Are Mobile Devices More Useful than Conventional Means as Tools for Learning Vocabulary?

Abstract: English as a Foreign Language (EFL) students face a daunting challenge. They must study and memorize literally thousands of words to achieve fluency. Knowledge of vocabulary not only allows for clearer expression, but also forms the foundation of language knowledge. Mobile devices such as smartphones and tablet PCs can potentially be effective learning tools, especially when used for developing the vocabulary of EFL students. While there are many good reasons to use technology to advance vocabulary learning, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…The results of the needs analysis showed that students' biggest weakness was learning and retention of English vocabulary. This finding is also reflected in other research studies [11][12].…”
Section: Resultssupporting
confidence: 87%
“…The results of the needs analysis showed that students' biggest weakness was learning and retention of English vocabulary. This finding is also reflected in other research studies [11][12].…”
Section: Resultssupporting
confidence: 87%
“…The findings of the needs analysis revealed that students' biggest weakness was learning and retention of English vocabulary. This need was also confirmed by other research studies, e.g., [11][12][13]26]. In addition, students wanted to learn and practice the words from their field of study, i.e., Management of Tourism.…”
Section: Resultsmentioning
confidence: 57%
“…Besides, they also increase EFL reading motivation (Lan, Sung, & Chang, 2007), stimulate learning outside the classroom (Liu, Lin, Tsai, & Paas, 2012), and promote game-based learning on mobile platforms (Klopfer, Sheldon, Perry, & Chen, 2012). As for foreign language learning, they help develop skills such as reading comprehension (Hsu, Hwang, & Chang, 2013;Khubyari & Narafshan, 2016), vocabulary learning and enhancement by means of vocabulary game-based applications (Huang & Huang, 2015;Lee, 2014) , including idiomatic expressions and collocations (Amer, 2010), and pronunciation, listening and conversation (Anaraki, 2009). MALL studies have focused mainly on L2 (second/foreign language) reading, writing, speaking and vocabulary development.…”
Section: Mobile Assisted Language Learning (Mall)mentioning
confidence: 99%